2015
DOI: 10.1175/jpo-d-14-0144.1
|View full text |Cite
|
Sign up to set email alerts
|

Global Wavenumber Spectrum with Corrections for Altimeter High-Frequency Noise

Abstract: The altimetry wavenumber spectra of sea surface height (SSH) provide a unique dataset for testing of geostrophic turbulence. While SSH spectral slopes of k−11/3 and k−5 are expected from theories and numerical simulations, the altimetry spectra from the original unfiltered and instrument noise–corrected data often are too shallow, falling between k−2 and k−3. In this study, the possibility that the flattened spectral slopes are partly due to contamination by unresolved high-frequency (<10 days) motions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 23 publications
4
43
0
Order By: Relevance
“…The local maximum of Linj in high‐energy predominantly eastward‐flowing currents, which is much obvious in Figures b and c, may be consistent with the results of global SSH spectrum analysis [ Xu and Fu , ; Zhou et al ., ]. Xu and Fu [] diagnosed the global variability of the spectrum using the altimeter‐observed SSH and found that SSH spectral slopes are deeper in the high EKE regions, such as the ACC, the Gulf Stream, and the Kuroshio Extension.…”
Section: Resultsmentioning
confidence: 99%
“…The local maximum of Linj in high‐energy predominantly eastward‐flowing currents, which is much obvious in Figures b and c, may be consistent with the results of global SSH spectrum analysis [ Xu and Fu , ; Zhou et al ., ]. Xu and Fu [] diagnosed the global variability of the spectrum using the altimeter‐observed SSH and found that SSH spectral slopes are deeper in the high EKE regions, such as the ACC, the Gulf Stream, and the Kuroshio Extension.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate white spectrum for scales between about 5 and 15 km is referred to as a spectral hump and is associated with blooms of normalized radar backscatter s 0 or rain contamination (Dibarboure et al 2014). While there have been suggestions for strategies to remove the spectral hump (e.g., Xu and Fu 2012;Zhou et al 2015) to obtain consistent spectral slopes, we opt not to apply these approaches here and instead truncate our spectral interpretation at about 30 km.…”
Section: Satellite Altimetry a The Saral/altika Altimetermentioning
confidence: 99%
“…Current altimeters provide measurements of SSH along the satellite track with a sampling frequency of 20 Hz, implying a spatial resolution on the order of ∼ 300 m. The power spectral density (PSD) of these measurements shows the presence of white noise (e.g., Le Traon et al, 2008;Fu, 2011, 2012;Dibarboure et al, 2014;Zhou et al, 2015), which is a major limiting factor for the estimation of ocean currents. Since noise has a stronger effect on small-scales it is common to (low-pass) filter altimetric measurements before computing velocities.…”
Section: Currents From Sea Surface Heightmentioning
confidence: 99%